Interview mit Dr. med. Hans Groth Verwaltungsratspräsident des World Demographic & Ageing Forum (WDA Forum), St. Gallen/Schweiz - Ovin, Rasto (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2022)
Interview with Dr. med. Hans Groth